2016
DOI: 10.3390/lubricants4030026
|View full text |Cite
|
Sign up to set email alerts
|

The Friction Reducing Effect of Square-Shaped Surface Textures under Lubricated Line-Contacts—An Experimental Study

Abstract: Surface texturing has been shown to be an effective modification approach for improving tribological performance. This study examined the friction reduction effect generated by square dimples of different sizes and geometries. Dimples were fabricated on the surface of ASP2023 steel plates using femtosecond laser-assisted surface texturing techniques, and reciprocating sliding line contact tests were carried out on a Plint TE77 tribometer using a smooth 52100 bearing steel roller and textured ASP2023 steel plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 23 publications
(23 reference statements)
1
26
0
Order By: Relevance
“…They suggested that this local friction response presumably is caused by the abrupt increase in film thickness. While similar local friction effects were observed in previous work by the current authors [47], that the friction drops as soon as the dimple array enters the contact area, and upward steps at trailing edge cause a friction increase. It should be noted that, in Vladescu's study, the relatively narrow and long rectangular pockets were fully covered in the contact area while sliding, whereas the previous work by the current authors was conducted with uncapped square dimples.…”
Section: Introductionsupporting
confidence: 90%
“…They suggested that this local friction response presumably is caused by the abrupt increase in film thickness. While similar local friction effects were observed in previous work by the current authors [47], that the friction drops as soon as the dimple array enters the contact area, and upward steps at trailing edge cause a friction increase. It should be noted that, in Vladescu's study, the relatively narrow and long rectangular pockets were fully covered in the contact area while sliding, whereas the previous work by the current authors was conducted with uncapped square dimples.…”
Section: Introductionsupporting
confidence: 90%
“…5. The non-textured results are adapted from a paper published by the current authors [33]. As shown in Fig.…”
Section: Friction Resultsmentioning
confidence: 99%
“…As has been discussed in papers published by current authors [32,33], dimples parameters (dimple depth, dimple diameter, depth-to-diameter ratio, and the texture density, dimple profiles (flat, spherical and linearly varying bottoms) and dimple shapes (circular, elliptical, rectangular, triangular and chevron shapes) have been studied in the past decades. Researchers have been aware of the benefit of anisotropically textured surfaces through numerical simulation, that the converging shape in the x-y plane (triangular dimples) and in the x-z plane (sloped bottom dimples) could both be reasons for enhancing the lubrication effects [34,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have looked at these two effects simultaneously (i.e. either surface topography's effect on oil consumption [4,5] or friction [6][7][8][9][10][11] have been studied). Their simultaneous investigation is necessary, since they are clearly interlinked.…”
Section: Piston Ring-liner Lubricationmentioning
confidence: 99%